Biosecurity infectious diseases of the returning Indonesian migrant workers - Irfan Wahyudi; Sri Endah Kinasih; Rachmah Ida; Toetik Koesbardiati; Mochamad Kevin Romadhona; Seokkyu Kim (Global Security: Health, Science and Policy)
Biosecurity is a crucial issue in a globalised world as today. Biosecurity has become a serious concern for some countries to prevent the transfer of any infectious diseases across borders. Involving human bio-surveillance, biosecurity regulation is actually an attempt to build new spatial demarcations in the border areas of countries. In the context of Indonesia, the biosecurity policy so far has been initiated and applied for protecting Indonesian borders from infectious disease transferred from the mobility of people, including Indonesian migrant workers when they returned back to this country. However, some important issues and controversies remain in debate, especially around the political economy discourses of the Indonesian government. This research, thus, focuses on the risk of disease transmission among the Indonesian migrant workers, which could affected not only Indonesia, but also others particular countries and global people’s health. This study examines the case of biosecurity issue in the border Island of Indonesia, which is Tanjung Pinang situated in Riau Islands. Tanjung Pinang is an offshore bordered area bordering to Singapore, Malaysia, Vietnam, and the Philippines. This place is part of a major maritime traffics lane between its neighbouring countries. Tanjung Pinang is also one of departure harbours for the Indonesian migrant workers to Malaysia and Singapore. Upon interviewing with migrant workers, the government representatives, and the NGOs/agents who have involved with migrant workers’ travels, this research found that biosecurity policy of the Indonesian government has not been implemented consistently and firm to the standard of health protocols; whilst, the prevention of infectious desease carried from migrant workers overseas who returned home could be spread out and brought health risks for domestic communities. The health authority in border area, i.e. Tanjung Pinang, has provided screening rooms; yet, the screenings were implemented for some random workers and on the workers’ physical body.